Model-Based Performance Prediction for Concurrent Software on Multicore Architectures A Simulation-Based Approach - Frank, Markus Kilian (The Karlsruhe Series on Software Design and Quality, 2022)
Model-based performance prediction is a well-known concept to ensure the quality of software.Current approaches are based on a single-metric model, which leads to inaccurate predictions for modern architectures. This thesis presents a multi-strategies approach to extend performance prediction models to support multicore architectures.We implemented the strategies into Palladio and significantly increased the performance prediction power.